(untitled) (Historia, 2022)
This article endeavours to make a significant contribution to the broadening of local school athletics history in Cape Town. By focusing on certain historical documents, the article explores the state and scope of athletics in black schools in Cape Town prior to 1956, a largely under-researched field in South African sport history. It does so by identifying prominent administrators, outstanding athletes, and participating schools. Many of these histories have disappeared or have been erased from public consciousness. The article shows how organised school athletics in Cape Town’s oppressed communities have been shaped by a myriad of teachers, politicians, and sport administrators of varying political and social backgrounds. It also provides details of the Trafalgar High School’s Wiener’s Day competitions. Next, a history of the Central School Sports Union and its offshoots is unpacked. Finally, the early years of the Western Province School Sports Board are overviewed. The article concludes by suggesting why it is important to reclaim this particular history. Opsomming Hierdie artikel wil ’n beduidende bydrae tot die verruiming van die plaaslike skole-atletiekgeskiedenis in Kaapstad lewer. Deur op sekere historiese dokumente te fokus, ondersoek die artikel die stand en omvang van swart skole-atletiek in Kaapstad voor 1956, ’n grootliks onontginde navorsingsveld in die Suid-Afrikaanse sportgeskiedenis. Vele prominente administrateurs, uitmuntende atlete en deelnemende skole wie se geskiedenisse uit die openbare bewussyn verdwyn het of daaruit gewis is, word in die proses geïdentifiseer. Die artikel toon aan hoe georganiseerde skole-atletiek in Kaapstad se onderdrukte gemeenskappe deur ’n groot aantal onderwysers, politici en sportadministrateurs uit verskillende politieke en sosiale agtergronde gevorm is. Dit verstrek verder besonderhede oor die Trafalgar High School se Wiener’s Day-kompetisies. Vervolgens word ’n geskiedenis van die Sentrale Skolesportunie en die vertakkings daarvan uiteengesit. Laastens word die beginjare van die Westelike Provinsie Skolesportraad oorsigtelik bespreek. Die artikel sluit af deur uit te wys waarom dit belangrik is dat hierdie spesifieke geskiedenis herwin word.